Load carrying capacity enhancement of cold formed steel walls using shotcreted steel sheets - KARAKALE, VAİL (ELSEVIER SCI LTD, 2012)
Recently worldwide cold formed steel buildings are recognized as viable alternatives to reinforced concrete buildings especially in seismic areas. This is because they are lightweight (easy to handle), fast constructed, energy efficient (green houses), economical, dimensionally stable and they do not need skilled worker. Under vertical loading the design principles of these buildings are well established and codified, however, under lateral loadings such as wind and earthquake loads efficiently design is needed. In this paper a new sheathing technique uses shotcreted ribbed steel sheets is proposed to improve the stability and increase the lateral load carrying capacities of the CFS walls in order to withstand earthquake and wind loads safely. The idea is to sheath the outer side of CFS structure external walls with thin ribbed steel sheets, then shotcreted the sheets with cement or gypsum mortars. To test the concept full size wall specimens were prepared in the laboratory and tested under monotonic vertical and lateral loads. Some of the specimens were sheathed with the traditional fiber cement boards or gypsum boards with mat reinforcement, while the others were sheathed with the proposed technique. Test results indicates that the lateral load carrying capacities of the walls sheathed with the proposed technique increases by about two times compared with the walls sheathed with traditional boards. And under ultimate loads they fail in local failure modes rather than overall buckling failure modes which commonly occur in the walls sheathed with traditional boards. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: CFS walls; Ribbed steel sheet; Shear wall; Seismic; Shotcrete; BEHAVIOR